The Problems of Teaching the Basics of Secular Ethics to Pedagogic Students - L. V. Shcheglova (Образование и наука)
The paper looks at the specialists training for teaching the Basics of Secular Ethics course in the secondary school. In author’s opinion, the above course is entitled to develop children’s moral consciousness. The subject is practical rather than descriptive, focused on the spiritual work, and teaching how to live in harmony with themselves and the surrounding world. The author emphasizes the difference between the secular and religious ethics related to the specificity of moral consciousness - based either on the principle of personal moral autonomy or theonomy in case of the religious ethics. The problematic task of developing the morally independent personality in the modern society is complicated by the confusion of ethics and etiquette, wide spread ideas of pluralism, relativism, infantilism and sense gratification. The challenges and inner contradictions of the given educational module are revealed in dealing with such concepts as the mercy and moral ideal. In conclusion, the author points out the significance of active positions of teachers and students alike in pursuing the Secular Ethics course.